FUNDRAISING WAKAF PESANTREN TEBUIRENG JOMBANG DAN GONTOR PONOROGO - Huda, Miftahul (LP2M IAIN Mataram, 2010)
This study describes the managerâs effort of waqf (endowment) to make it productive. The study focuses on the ways in which the waqf manager (nadzir) endeavors to get or expand funds to support for the pesantrenâs independence. Using qualitative method, this field research examines the waqf management in two pesantrens as a cases study in Tebuireng in Jombang and Gontor in Ponorogo, both in East Java. The study finds three models of endowment management; first, the manager uses available potential waqf funds or appointing a new manager. Second, the manager creates new resources taken from productive waqf funds, and third, monetizes non-financial waqf resources.